Urine ethyl glucuronide and ethyl sulphate using liquid chromatography-tandem mass spectrometry in a routine clinical laboratory. (January 2017) - Armer, Jane M; Allcock, Rebecca L
Background: Detection of alcohol consumption in clients undergoing treatment for alcohol dependence can be difficult. The ethanol metabolites ethyl glucuronide and ethyl sulphate are detectable for longer in urine than either breath ethanol or urine ethanol. Our aim was to develop a liquid chromatography-tandem mass spectrometry method for urine ethyl glucuronide and ethyl sulphate for use in a routine clinical laboratory and define clinical cut-offs in a large population who had not consumed alcohol for at least two weeks. Methods: Urine samples were diluted in 0.05% formic acid in HPLC grade water and then directly injected onto a Waters Acquity ultra high performance liquid chromatography coupled to a Waters TQ Detector. Eighty participants were recruited who had not consumed alcohol for at least two weeks to define cut-offs for urine ethyl glucuronide and ethyl sulphate. Samples and alcohol diaries were also collected from 12 alcohol-dependent clients attending a treatment programme. Results: The assay was validated with a lower limit of quantitation of 0.20 mg/L for ethyl glucuronide and 0.04 mg/L for ethyl sulphate. Accuracy, precision, linearity and recovery were acceptable. Cut-offs were established for ethyl glucuronide, ethyl sulphate and ethyl sulphate/creatinine ratio (≤0.26 mg/L, ≤0.22 mg/L and ≤0.033 mg/mmol, respectively) in a non-drinking population. The validated cut-offs correctly identified clients in alcohol treatment who were continuing to drink alcohol. Conclusions: A simple liquid chromatography-tandem mass spectrometry method for urine ethyl glucuronide and ethyl sulphate has been validated and cut-offs defined using 80 participants who had not consumed alcohol for at least two weeks. This is the largest study to date to define cut-offs for ethyl glucuronide, ethyl sulphate and ethyl sulphate/creatinine ratio.